Sally's Phone - Lindop, Christine; Illustrated by Reece, Gavin (Oxford, New York Oxford University Press, 2008)
Word count 1,400 Bestseller
Include Color Illustration
Keywords: Readers (Adult) -- English language--Study and teaching -- Cell phones